An angle speed and thrust relationship of the rotor system in the quadcopter aircraft - Al Al; Arfita Yuana Dewi; Antonov Bachtiar; Dwi Harinita (Institute of Advanced Engineering and Science, 2019)
Utilizing Quadcopter were still many obstacles such as; plane easy to fall; the battery is not durable; vulnerable to weather conditions and others. The research and development has grown to improve aircraft facilities and capabilities. Many parameters related to aircraft lift capability factors; fly long; flying high; type of motor; the type of propeller: including the sensors and control systems used. This study was to find the relationship between changes in the BLDC motor voltage source to the rotor angle velocity (ω); rotor speed to rotor lift (Ft); wind speed to rotor lift; push the following rotor (Ct). Empirical testing was conducted in the laboratory to find the relationship of these parameters. The results data show that; the lift power generated with rotational speed was not proportional, non linearity occurs when the rotor was released from the self and starts pulling the strain gauge when the rotation speed reaches around 65 rps. Once the rotation speed of the rotor is able to reach up to 1.5 Newton lift then the thrust rising trend sharply increasing toincreasing of the rotor speed. A motor hade 1200 KV and blade with a radius of 0.12 m, then obtained thrust (Ct) of 1.732.